2020
DOI: 10.1126/sciadv.abb7369
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic metal-polymer interaction for the design of chemoselective and long-lived hydrogenation catalysts

Abstract: Metal catalysts are generally supported on hard inorganic materials because of their high thermochemical stabilities. Here, we support Pd catalysts on a thermochemically stable but “soft” engineering plastic, polyphenylene sulfide (PPS), for acetylene partial hydrogenation. Near the glass transition temperature (~353 K), the mobile PPS chains cover the entire surface of Pd particles via strong metal-polymer interactions. The Pd-PPS interface enables H2 activation only in the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 39 publications
0
58
0
9
Order By: Relevance
“… Stability (h) Refs. NHC–Cu C 2 H 2 /C 2 H 4 (1/99) 25 9.6 × 10 5 2.1 × 10− 2 >99 ~30 100 This work Cu 1 /ND@G C 2 H 2 /C 2 H 4 /H 2 /He (1/20/10/69) 200 3 × 10 3 1.7 × 10− 3 >98 500 60 48 Ni 3 Ga C 2 H 2 /C 2 H 4 /H 2 /He (0.5/50/10/39.5) 200 4 × 10 4 1.4 × 10 −6 77 500 50 49 Al 13 Fe C 2 H 2 /C 2 H 4 /H 2 /He (0.5/50/5/44.5) 200 9 × 10 4 / 82 1000 20 50 Pd/PPS C 2 H 2 /C 2 H 4 /H 2 /C 3 H 8 /N 2 (0.6/49.3/0.9/0.6/48.6) 100 3.26 × 10 2 / >65 60 200 51 Pd@SOD C 2 H 2 /H 2 /N 2 (0.6/6/93.4) 150 3 × 10 4 / 94.5 12 50 7 Single–atom Pd C 2 H 2 /C 2 H 4 /H 2 /He (0.5/50/5/44.5) 120 …”
Section: Resultsmentioning
confidence: 99%
“… Stability (h) Refs. NHC–Cu C 2 H 2 /C 2 H 4 (1/99) 25 9.6 × 10 5 2.1 × 10− 2 >99 ~30 100 This work Cu 1 /ND@G C 2 H 2 /C 2 H 4 /H 2 /He (1/20/10/69) 200 3 × 10 3 1.7 × 10− 3 >98 500 60 48 Ni 3 Ga C 2 H 2 /C 2 H 4 /H 2 /He (0.5/50/10/39.5) 200 4 × 10 4 1.4 × 10 −6 77 500 50 49 Al 13 Fe C 2 H 2 /C 2 H 4 /H 2 /He (0.5/50/5/44.5) 200 9 × 10 4 / 82 1000 20 50 Pd/PPS C 2 H 2 /C 2 H 4 /H 2 /C 3 H 8 /N 2 (0.6/49.3/0.9/0.6/48.6) 100 3.26 × 10 2 / >65 60 200 51 Pd@SOD C 2 H 2 /H 2 /N 2 (0.6/6/93.4) 150 3 × 10 4 / 94.5 12 50 7 Single–atom Pd C 2 H 2 /C 2 H 4 /H 2 /He (0.5/50/5/44.5) 120 …”
Section: Resultsmentioning
confidence: 99%
“…[3] These materials may include hypercrosslinked polymers, [4] covalent organic frameworks (COFs), [5] conjugated microporous polymers (CMPs), [6] covalent triazine frameworks (CTFs), [7] and engineering plastics. [8] Being composed of mainly sp 2 carbons,t hese polymers exhibit remarkably improved thermochemical stabilities compared to typical organic polymers.S oft organic polymers with nanoscale framework mobility can have unique potentials as catalyst supports compared to hard inorganic materials.F or instance, we recently demonstrated that mobile polyphenylene sulfide (PPS) chains can coat the Pd catalyst surface via the phenomena denoted as dynamic metal-polymer interaction (DMPI). [8] DMPI indicates as trong interaction between metal catalysts and mobile polymer chains at relatively mild temperatures.T he PPS overlayer on the Pd surface formed via DMPI regulated the adsorption of reactants and their surface reactions,s ignificantly enhancing the selectivity and catalyst lifetime in partial hydrogenation reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the characteristics of our new frameworks: high surface area, good dispersion of the metals and weak and reversible binding to the metal cations; we hypothesized that they could be used as supports for noble metal sites. Similar materials including carbon nitride 46,47 or even PPS 48 have been used as supports to stabilize and modify catalytic activity of Pd in catalysis. Gratifyingly, Pd 2+ @P1 showed good catalytic activity for classical Pd-catalysed reactions, i.e.…”
Section: Catalytic Application Of Pd@p1mentioning
confidence: 99%